First serosurvey of Besnoitia spp. infection in wild European ruminants in Spain - Gutiérrez-Expósito, D.; Marco, Ignasi; Boadella, Mariana; Gortázar, Christian; Álvarez-García, Gema (Veterinary Parasitology, 2013)
et al. Besnoitia besnoiti has been reported to affect cattle, wildebeest, kudu and impala, and B. tarandi other wild ruminants (caribou, reindeer, mule deer and musk ox), causing similar characteristic clinical signs and lesions. However, both Besnoitia species have been reported in different geographical areas and the link between the sylvatic and domestic life cycles of Besnoita spp. in wild ruminants and cattle remains unknown. The aim of this study was to evaluate the presence of specific antibodies against Besnoitia spp. in wild ruminants in Spain. A wide panel of sera from red deer (Cervus elaphus) (n = 734), roe deer (Capreolus capreolus) (n = 124), chamois (Rupicapra pyrenaica) (n = 170) and mouflon (Ovis musimon) (n = 20) collected from different locations of Spain was analyzed. Beef cattle were present in all sampled areas and, interestingly, bovine besnoitiosis has been widely reported in some of them (e.g., Pyrenees and Central Spain). Sera samples were first examined with an Enzyme-Linked Immunosorbent Assay (ELISA). For red deer and roe deer, the ELISA was standardized with positive and negative control sera from several Cervidae species (100% Se and 98% Sp). Chamois and mouflon sera samples were tested with a previously reported ELISA validated for bovine sera (97% Se and 95% Sp) using protein G as a conjugate. Positive results by ELISA were confirmed a posteriori with a tachyzoite-based Western blot. Sixty-one sera samples from red deer and 17 sera samples from roe-deer were seropositive or doubtful by ELISA. All samples from mouflon were seronegative and 15 sera samples from chamois were considered doubtful. B. besnoiti exposure was only confirmed clearly by Western blot in one red deer and one roe deer from the Spanish Pyrenees where the disease is traditionally endemic. This is the first serological report of Besnoitia spp. infection carried out in European wild ruminants and the results show that specific antibodies are present at least in red deer and roe-deer. Thus, wild ruminants from ...